Gain-clamped double-pass S-band erbium-doped fiber amplifier - Harun, Sulaiman Wadi; Rahman, Muhammad Sabri Abdul; Ahmad, Harith (2005)
Gain clamping in double-pass short-wavelength band erbium-doped fiber amplifier (S-band EDFA) is demonstrated. It uses a fiber Bragg grating, which operates in conventional-band to form an oscillating laser in the cavity using an erbium-doped fiber (EDF) gain at around 1530 nm. This new technique has shown a good gain clamping effect with gain variation of less than 1.0 dB from -40 to -14 dBm input signal powers for 1500 nm signal. The gain can be controlled within 18 to 20 dB by varying a variable optical attenuator from 0 to 8 dB. Compared with an unclamped amplifier, the noise figures for small signals are slightly improved due to the suppression of amplified spontaneous emission (ASE). However, the noise figure level is still considerably high due to the double-pass scheme and unoptimised splicing between a depressed cladding EDF and a standard single mode fiber. The advantage of this gain clamped amplifier is that the oscillating light operates at wavelength outside S-band region, which prevent the wavelength division multiplexed system from being disturbed.